Hydrogen production by the water-gas shift reaction using CuNi/Fe2O3 catalyst - Jha, Ajay; Jeong, Dae-Woon; Shim, Jae-Oh; Jang, Won-Jun; Lee, Yeol-Lim; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Science & Technology, 2015)
Incorporation of both Cu and Ni together into the crystalline lattice of Fe2O3 results in a significant increase in the catalytic activity and also suppresses the methanation reaction in the high-temperature water-gas shift (HT-WGS) reaction. CuNi/Fe2O3 exhibited the highest CO conversion with negligible CH4 selectivity at the extremely high GHSV of 101 000 h(-1) (X-CO = 85% at 400 degrees C). The high activity of CuNi/Fe2O3 catalyst is mainly due to the increase in the lattice strain and the decrease in the binding energy of lattice oxygen. In addition, X-ray photoelectron spectroscopy (XPS) results provide direct evidence for the formation of surface CuNi alloy, which plays a critical role in suppressing the methanation reaction. The detailed characterization by powder X-ray diffraction (XRD), XPS, BET, and H-2 temperature-programmed reduction (TPR) techniques was used to understand the role of dopants on host iron oxides in the enhancement of catalytic activity for HT-WGS reaction.